2013
DOI: 10.1117/1.jmm.12.2.023013
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet mask defect inspection with a half pitch 16-nm node using simulated projection electron microscope images

Abstract: Abstract. According to an International Technology Roadmap for Semiconductors (ITRS-2012) update, the sensitivity requirement for an extreme ultraviolet (EUV) mask pattern inspection system is to be less than 18 nm for half pitch (hp) 16-nm node devices. The inspection sensitivity of extrusion and intrusion defects on hp 64-nm line-andspace patterned EUV mask were investigated using simulated projection electron microscope (PEM) images. The obtained defect images showed that the optimization of current densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…[4][5][6][7] In order to accelerate this development program, the optimal inspection condition was investigated by using a computer simulation. [8][9][10][11] We already reported that 16-nm-sized defect on hp 64-nm mask pattern was detectable with a 10-times higher signal intensity than that of the standard deviation of the background intensity level by using the PEM technique when the Ru capped multilayer (ML) was used in EUV mask, 9 and the simulated detectability was found to be in good agreement with experimental results. 7 It was also found that the sensitivity of defect detection was predictable by measuring the secondary electron yield curves of a Ta-based absorber layer and Ru-capped ML.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…[4][5][6][7] In order to accelerate this development program, the optimal inspection condition was investigated by using a computer simulation. [8][9][10][11] We already reported that 16-nm-sized defect on hp 64-nm mask pattern was detectable with a 10-times higher signal intensity than that of the standard deviation of the background intensity level by using the PEM technique when the Ru capped multilayer (ML) was used in EUV mask, 9 and the simulated detectability was found to be in good agreement with experimental results. 7 It was also found that the sensitivity of defect detection was predictable by measuring the secondary electron yield curves of a Ta-based absorber layer and Ru-capped ML.…”
Section: Introductionsupporting
confidence: 73%
“…The authors had already reported that a similar phenomenon was observed in the case of Ru-capped ML. 9 In the case of the intrusion defect, because the aspect ratio of the smaller defect becomes higher, the elevation angle of the defect becomes narrower as defect size gets smaller. Therefore, the signal from the bottom of the intrusion defect becomes weaker as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] In the pattern inspection system, the signal-to-noise ratio (SNR) is another critical parameter as it affects the defect detection sensitivity and minimizes false defect detection. 9 At higher illumination beam current densities, where a larger number of electrons per pixel is obtained on the detector, a higher SNR is achieved. However, high current densities of a focused illumination beam degrade the resolution due to blurring caused by the space charge effect.…”
mentioning
confidence: 99%